Consequences of daily corticosteroid dosing with or without pre-treatment with quinidine on the in vivo cytochrome P450 2D (CYP2D) enzyme in rats: effect on O-demethylation activity of dextromethorphan and expression levels of CYP2D1 mRNA. (2nd January 2018) - Giri, Poonam; Delvadia, Prashant; Gupta, Laxmikant; Patel, Nirmal; Trivedi, Priyal; Lad, Krishna; Patel, Hiren M.; Srinivas, Nuggehally R.
Abstract: 1. Present investigation was carried out in rats to study influence of corticosteroids after repeated dosing with/without pre-treatment with CYP2D inhibitor quinidine on the CYP2D1 mRNA levels and CYP2D enzyme activity using dextromethorphan as probe substrate. 2. CYP2D1 mRNA was measured in liver homogenate using quantitative real-time polymerase chain reaction [qRT-PCR] and enzymatic reaction was studied ex vivo in liver S-9 fractions of rats treated with oral 10 mg/kg dexamethasone or prednisolone for five days or pre-treated with quinidine and followed by treatment with oral 10 mg/kg corticosteroids for five days. 3. Five days repeat dosing of dexamethasone or prednisolone decreased the activity of the rat liver CYP2D by 37% and 34%, at 30 min incubation and decreased CYP2D1 mRNA levels by 62% and 61%, respectively. 4. Pre-treatment of quinidine decreased the enzymatic activity of rat CYP2D by 58% and did not potentiate CYP2D inhibition by corticosteroids. This observation was further complemented by qRT-PCR data. 5. Corticosteroids caused CYP2D inhibition in rats vs. literature evidence of CYP2D induction in human hepatocytes/pregnant humans demonstrating lack of concordance. In vivo inhibition should be factored for interpretation of pharmacokinetic data of CYP2D substrates when treated with corticosteroids in rats.